ABJ correlators with weakly broken higher spin symmetry - Binder,DJ; Chester,SM; Jerdee,M (Journal of High Energy Physics, 2021)
A bstract We consider four-point functions of operators in the stress tensor multiplet of the 3d $$ \mathcal{N} $$ N = 6 U( N ) k × U( N + M ) −k or SO(2) 2 k × USp(2 + 2 M ) −k ABJ theories in the limit where M and k are taken to infinity while N and λ ∼ M/k are held fixed. In this limit, these theories have weakly broken higher spin symmetry and are holographically dual to $$ \mathcal{N} $$ N = 6 higher spin gravity on AdS 4 , where λ i